The three musketeers - Dumas, Alexandre, 1802-1870 (Modern Library, 2001)
"First published in 1844, Alexandre Dumas's swashbuckling epic chronicles the adventures of D'Artagnan, a gallant young nobleman who journeys to Paris in 1625 hoping to join the ranks of musketeers guarding Louis XIII. He soon finds himself fighting alongside three heroic comrades - Athos, Porthos, and Aramis - who seek to uphold the honor of the king by foiling the wicked plots of Cardinal Richelieu and the beautiful spy "Milady." As Clifton Fadiman reflected, "We read The Three Musketeers to experience a sense of romance and for the sheer excitement of the story. In these violent pages all is action, intrigue, suspense, surprise - an almost endless chain of duels, murders, love affairs, unmaskings, ambushes, hairbreadth escapes, wild rides. It is all impossible and it is all magnificent.""--Jacket.